Loneliness Among Adult with Visual Impairment - Tresa Ivani Saskia (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2021)
Loneliness is a multifaceted experience which can be understood through the lens of the biopsychosocial model which is an interdisciplinary approach that looks at the interconnection between biology, psychology, and socio-environmental factors in affecting health, illness, psychological experiences and disturbances. This study compared the qualitative dimensions of loneliness between blind and visually impaired persons and the general population, rather than the frequency or intensity of their loneliness. To the best of our knowledge, no studies have specifically evaluated depression in young and middle-aged people with visual impairment (VI). Discrimination may exacerbate these difficulties. High prevalence of loneliness among the visually impaired elderly persons, that reports a prevalence of 54% in the visually impaired elderly aged ≥55 years. In addition, the risk of loneliness was higher for those who were aged 36 to 50 years, exposed to bullying or physical or sexual abuse, had blindness, other impairments, or were unemployed. The mean score for loneliness was 4.83 (SD 1.82), 4.88 for women and 4.78 for men (p = 0.46). The majority of participants reported missing somebody to be with sometimes (39.0%) or often (21.1%). The aim of this study to estimate the prevalence of loneliness and associated factors in adults with visual impairment.